Alleviation of heavy metal stress by arbuscular mycorrhizal symbiosis in Glycine max (L.) grown in copper, lead and zinc contaminated soils - Adeyemi, Nurudeen Olatunbosun; Atayese, Mufutau Olaoye; Sakariyawo, Olalekan Suleiman; Azeez, Jamiu Oladipupo; Abayomi Sobowale, Soremi Paul; Olubode, Adebanke; Mudathir, Ridwan; Adebayo, Rukayat; Adeoye, Samuel (Rhizosphere, 2021)
There are few reports on the use of arbuscular mycorrhizal fungi (AMF) to promote growth and stress tolerance of soybean (Glycine max L.) in agricultural soils contaminated with heavy metals. The present study evaluated the role of AMF in promoting tolerance and growth, as well as uptake of heavy metals in shoots of soybean plants. Soybean plants were inoculated with AMF (Funneliformis mosseae) in a pot experiment polluted with different concentrations of heavy metals [copper (Cu), lead (Pb) and zinc (Zn)] as well as their combination. The tested AMF inoculum promoted the soybean growth and seed yield. Increased colonization of the soybean roots improved the soybean growth through increased phosphorus uptake and accumulation in the plant tissues by 68.8%. The results showed that soybean grown in the contaminated soils inoculated with AMF were more tolerant in alleviating the metals toxicity by retaining the heavy metals in the roots, thereby reducing translocation of Cu, Pb and Zn by 21.8, 57.6 and 67.3% respectively in the aerial part of the plant and improving the overall plant productivity by 59.1%. The findings provide evidence of the potential of AMF in phytoremediation of agricultural soils contaminated with toxic metals.